PRIORITAS PENGEMBANGAN DTW BAHARI DI KAWASAN PESISIR UTARA KABUPATEN SIKKA, PROVINSI NUSA TENGGARA TIMUR - Ida Bagus Gede Agung Widana; Angelita Peridibua Mudamakin; I Made Subrata (JURNAL KEPARIWISATAAN, 2022)
Sikka Regency is one of the regencies on Flores Island, East Nusa Tenggara Province which has advantages in marine tourism. Geographically, Sikka Regency has two coastal areas, namely the northern coastal area and the southern coastal area. There are 3 (three) beach locations on the north coast that are the focus of research, namely Kajuwulu Beach, Nusa Kutu Beach and Wairterang Beach. The aim of this study is to determine the priority of the development of the northern coastal area of ??Sikka Regency in terms of 4 (four) A criteria (Attraction, Accessibility, Amenities and Ancillary Services). The sampling technique used was purposive sampling, snowball sampling and quota sampling with 9 informants for the study who were tourism stakeholders consisting of the Government, Society, Media, Academics, and Tourism Entrepreneurs. The data analysis technique used in this research is qualitative data analysis using the Analytic Hierarchy Process (AHP) method. The results show that Kajuwulu Beach is the main priority for developing marine tourism attractions, followed by Nusa Kutu Beach in second place and the last is Wairterang Beach. The determination of Kajuwulu Beach as a top priority marine tourism attraction is influenced by the criteria for Amenities and Ancillary Services.